Actinobacteria from Arid and Desert Habitats: Diversity and Biological Activity - Mohammadipanah, Fatemeh; Wink, Joachim (Frontiers in Microbiology, 2016)
The lack of new antibiotics in the pharmaceutical pipeline guides more and more researchers to leave the classical isolation procedures and to look in special niches and ecosystems. Bioprospecting of extremophilic Actinobacteria through mining untapped strains and avoiding resiolation of known biomolecules is among the most promising strategies for this purpose. With this approach, members of acidtolerant, alkalitolerant, psychrotolerant, thermotolerant, halotolerant and xerotolerant Actinobacteria have been obtained from respective habitats. Among these, little survey exists on the diversity of Actinobacteria in arid areas, which are often adapted to relatively high temperatures, salt concentrations, and radiation. Therefore, arid and desert habitats are special ecosystems which can be recruited for the isolation of uncommon Actinobacteria with new metabolic capability. At the time of this writing, members of Streptomyces, Micromonospora, Saccharothrix, Streptosporangium, Cellulomonas, Amycolatopsis, Geodermatophilus, Lechevalieria, Nocardia, and Actinomadura are reported from arid habitats. However, metagenomic data present dominant members of the communities in desiccating condition of areas with limited water availability that are not yet isolated. Furthermore, significant diverse types of polyketide synthase (PKS) and non-ribosomal peptide synthetase (NRPS) genes are detected in xerophilic and xerotolerant Actinobacteria and some bioactive compounds are reported from them. Rather than pharmaceutically active metabolites, molecules with protection activity against drying such as Ectoin and Hydroxyectoin with potential application in industry and agriculture have also been identified from xerophilic Actinobacteria. In addition, numerous biologically active small molecules are expected to be discovered from arid adapted Actinobacteria in the future. In the current survey, the diversity and biotechnological potential of Actinobacteria obtained from arid ecosystems, along with the recent work trend on Iranian arid soils, are reported.